Cybersecurity Vulnerabilities in Digital Business: Challenges, and Novel Directions for Resilience - Adiguna, Vinsent Brilian; Inabah, Sekar Farahdila; Rachel, Rona (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Digital transformation has profoundly reshaped business ecosystems by embedding advanced technologies into operations, customer engagement, and decision-making processes. However, this transformation simultaneously amplifies cybersecurity vulnerabilities that endanger organizational resilience, data integrity, and consumer trust. This study provides a comprehensive analysis of cybersecurity vulnerabilities in digital business environments based on an extensive review of open-access literature and real-world case studies. The findings indicate that 89% of companies face web application vulnerabilities, 93% experience hosting and configuration issues, and 46% of employees reuse breached passwords—revealing persistent weaknesses in digital infrastructures. These vulnerabilities result in financial losses, reputational damage, and regulatory non-compliance that may threaten long-term business continuity. Artificial Intelligence (AI) has emerged as both a catalyst for advanced cyberattacks and a strategic defense enabler. AI-driven threat intelligence, anomaly detection, and automated response mechanisms significantly enhance organizational capacity to predict, prevent, and mitigate cyber incidents. The case of SAP NetWeaver zero-day exploitation (CVE-2025-31324) demonstrates the urgency of adaptive defense frameworks, while the implementation of AI-based zero-trust architectures highlights the importance of continuous verification and risk-based access control. This research recommends adopting AI-augmented cybersecurity solutions, strengthening supply chain security, and fostering cyber-aware organizational cultures to ensure sustainable digital resilience. Additionally, it underscores the necessity of aligning cybersecurity with business strategies through cross-disciplinary collaboration that integrates technology, management, human behavior, and policy. By linking cyber resilience directly with organizational performance and strategic competitiveness, this study contributes a holistic framework for maintaining trust and stability in the rapidly evolving landscape of digital business.